An efficient system for bioconjugation based on a widely applicable engineered O-glycosylation tag <subtitle>Short title: Controlled bioconjugation via O-glycan engineering</subtitle> - Thomas V. Murray; Kasia Kozakowska-McDonnell; Adam Tibbles; Annabel Taylor; Daniel Higazi; Emmanuel Rossy; Alessandra Rossi; Sivaneswary Genapathy; Giulia Tamburrino; Nicola Rath; Natalie Tigue; Vivian Lindo; et al. (Taylor & Francis Group, 2021)
Bioconjugates are an important class of therapeutic molecules. To date, O-glycan-based metabolic glycoengineering has had limited use in this field, due to the complexities of the endogenous O-glycosylation pathway and the lack of an O-glycosylation consensus sequence. Here, we describe the development of a versatile on-demand O-glycosylation system that uses a novel, widely applicable 5 amino acid O-glycosylation tag, and a metabolically engineered UDP-galactose-4-eperimase (GALE) knock-out cell line. Optimization of the primary sequence of the tag enables the production of Fc-based proteins with either single or multiple O-glycans with complexity fully controlled by media supplementation. We demonstrate how the uniformly labeled proteins containing exclusively N-azido-acetylgalactosamine are used for CLICK chemistry-based bioconjugation to generate site-specifically fluorochrome-labeled antibodies, dual-payload molecules, and bioactive Fc-peptides for applications in basic research and drug discovery. To our knowledge, this is the first description of generating a site-specific O-glycosylation system by combining an O-glycosylation tag and a metabolically engineered cell line.